Etimologijos pastabos IV: váikščioti - Smoczyński, Wojciech (Baltistica, 1995)
ETYMOLOGICAL REMARKS IV: váikščiotiDescriptively, Lith. váikščioti (-ioja) „walk, stroll, pace” may be analysed as váik-ščioti (cf. vỹkti, -sta „go, make one’s way”, veĩkti, -ia „do act, operate”) that seems to have substituted for older *vaik-čioti owing to reanalysis of forms where -š- was part of a root.Diachronically, in view of dial. váikštyti (váikšto) „walk, stroll, pace” š after k), originally a causative from iš-vykstù „I go away, leave, depart”, it is likely that 3 p. praes. *vaikst-i̯a > *vaikščia served as a basis for váikščioja, váikščioti, an iterative with the suffix -oti.
Keywords: etimologija; lietuvių kalba; vaikščioti